Peran Pancasila untuk Berbangsa dan Bernegara - Mandela, Alistia; Azzalia, Nayla; Fadilah, Ahmad Arif (TSAQOFAH, 2025)
Pancasila is the foundation and guideline for life of the Indonesian nation and contains five important values ​​which are the goals of the country. The story of the birth of Pancasila reflects the processes and dynamics that occurred in Indonesian society both before independence and during the independence and Old Order era. In this context, Pancasila is not only seen as the basis of the state, but also as a moral and ethical guideline for the state and behavior. This researcher examines the role of Pancasila in the state and country. The aim of this research is to provide an overview of the role of Pancasila for the nation and state. The research method used is using a type of library research, which is related to writing methods and library data by obtaining information through secondary data collection in the form of journals and other sources that support and will be discussed in this research. The research results obtained are that there are many values ​​from Pancasila which can become the role of Pancasila for the nation and state. So this article can be used as a reference for implementing Pancasila values ​​in everyday life.